1974
DOI: 10.1002/1097-0142(197403)33:3<732::aid-cncr2820330319>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating lipomas and angiolipomas revisited

Abstract: Twenty‐seven soft tissue tumors composed of benign adipose tissue are presented featuring extensive local invasion and recurrence. Infiltrating angiolipomas and infiltrating lipomas are two distinct entities with different clinical and histologic features. The surgical approach demands wide local excision assisted by frozen section analysis to assure adequacy of removal. Extensive histologic sampling is mandatory to demonstrate the infiltrative character of the tumor and yet eliminate from consideration liposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
0
4

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(82 citation statements)
references
References 34 publications
5
73
0
4
Order By: Relevance
“…It is also reported that the intramuscular location of a lipoma is a risk factor for malignancy [1]. In our patient the lesion non infiltrated the muscle planes, but was strictly adhesed to the muscular fascia [3].…”
Section: Discussionsupporting
confidence: 52%
“…It is also reported that the intramuscular location of a lipoma is a risk factor for malignancy [1]. In our patient the lesion non infiltrated the muscle planes, but was strictly adhesed to the muscular fascia [3].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, despite a proven negative imaging, a liposarcoma may still be malignant. Therefore, careful histopathologic evaluation is required, and the presence of nuclear pleomorphism and multinuclear giant cells may help to distinguish lipomas from malignant liposarcomas (18).…”
Section: Discussionmentioning
confidence: 99%
“…The local recurrence rate of IML has been reported to range from 19 to 62.5%, and the time between surgery and lesion reappearance has been reported to be an average of 6 to 7.5 years [2,32]. No malignant changes have been reported for recurrent IMLs [32].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in less than 2% of all lipomas [2] and is extremely rare in oral and maxillofacial regions [3,4]. Since a local recurrence rate ranging from 19% to 62.5% after surgical excision has been reported in some literature [2,5], wide local excision and appropriate clinical monitoring of patients are mandatory [5].…”
Section: Introductionmentioning
confidence: 99%